The engineer's instruction to provide the wall and floor penetration,opening, sleeve,groove etc. as per drawings - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the the engineer's instruction to provide the wall and floor penetration ,opening, sleeve, groove etc. as per drawings of BRACU new campus project site.